Synergy of Oxygen Plasma and Al2O3 Atomic Layer Deposition on Improved Electrochemical Stability of Activated Carbon-Based Supercapacitor - Zhang, Fuming; Song, Guanghui; Gandla, Dayakar; Ein-Eli, Yair; Tan, Daniel Q. (Frontiers in Energy Research, 2021)
As a conventional electrode material of electric double-layer capacitors (EDLC), activated carbon (AC) still faces challenges to exhibit high capacitance. To address this problem, herein, we introduce a combined method of oxygen plasma and Al2O3 tomic layer deposition (ALD) on AC electrodes to reduce the impedance and improve the cycle stability of EDLC. The defect structure can be precisely designed by simply tuning the oxygen-plasma treatment time, thereby affecting the microstructures of AC electrode. Such a tactic permits the first-operated AC electrode with more defects and the ALD passivation of AC resulting in an outstanding rate performance for the device (40.6 F g–1 at 5 mA cm–2, 20.1 Fg–1 at 100 mA cm–2) and cycling stability (∼90% retention after 5,000 cycles). This benefit from the synergistic effect of defects from doped oxygen and stable aluminum oxide layer on the electrode surface. This work delivers a feasible strategy to construct a stable AC material with superior cycling performance for supercapacitor.